Degradasi Moral Ditinjau dari Perspektif Pendidikan Agama Islam - Nora Karima Saffana; Muhammad Rifa’i Subhi (https://ejournal.insuriponorogo.ac.id/, 2023)
Changing times towards the 21st century are now bringing every level of society to advances in science and technology. However, advances in science and technology that should be able to create a civil society have actually eroded the importance of moral values, good teachings about actions and behavior or what we often call morals. So to overcome moral degradation, there are efforts that must be made, one of which is by instilling Islamic educational values ​​in families, schools and society as early as possible. This is important because if there is no habituation as early as possible, it will be very difficult to apply the values ​​of Islamic education when he grows up. This research aims to determine the urgency of Islamic Religious Education in facing moral degradation. To overcome moral degradation, efforts must be made, one of which is by instilling character education in the family, school and community from as early as possible. This research is qualitative research using a literature study method using sources from journal articles, books, websites and other relevant sources. The results of this research show that Islamic Religious Education plays an important role in dealing with the problem of moral degradation, namely: 1) Islamic Religious Education as a strategy to increase the potential for creating moral humans, 2) Islamic Religious Education as a revitalization of character education, 3) Islamic Religious Education in forming society madani.